2008
DOI: 10.1089/lap.2006.0131
|View full text |Cite
|
Sign up to set email alerts
|

Hand-Assisted Laparoscopic Nephroureterectomy (HALNU): An Assessment of the Impact of Obesity in 50 Procedures

Abstract: HALNU is an effective surgical treatment for patients with BMIs as great as 45.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…This study is also the first to associate age, race, ECOG performance status, CKD stage and CCI score as independent predictors of peri‐operative complications. Lastly, similarly to other studies, we also found that BMI was not a factor in operation duration, estimated blood loss and complications rates . Given the rarity of UTUC, it is unlikely that a randomized trial examining peri‐operative outcomes of RNU will be conducted.…”
Section: Discussionsupporting
confidence: 84%
“…This study is also the first to associate age, race, ECOG performance status, CKD stage and CCI score as independent predictors of peri‐operative complications. Lastly, similarly to other studies, we also found that BMI was not a factor in operation duration, estimated blood loss and complications rates . Given the rarity of UTUC, it is unlikely that a randomized trial examining peri‐operative outcomes of RNU will be conducted.…”
Section: Discussionsupporting
confidence: 84%
“…Patients who received neoadjuvant chemotherapy had a significantly higher median BMI than patients who underwent LNUX alone, suggesting that these patients may have been prone to a higher rate of adverse events; however, previous studies have shown that LNUX can be performed without significant differences in operative time, estimated blood loss, or complication rates among groups of patients with BMIs as high as 45. 23 The patients in the current study had estimated blood loss values, operative times, and lengths of hospital stays that were well within the ranges reported in various previous studies .7 , 9 , 13 , 24 , 25 Although the overall complication rates in the current study were higher than those previously reported, previous studies did not use the Clavien system or a similar systematic scale to grade complications; thus, some complications-predominantly those considered to be lower grade-may not have been included in the previous studies' measured rates.…”
Section: Commentmentioning
confidence: 99%